Coexistence of Heavy Metal Tolerance and Antibiotic Resistance in Thermophilic Bacteria Belonging to Genus Geobacillus - Najar, Ishfaq Nabi; Das, Sayak; Kumar, Santosh; Sharma, Prayatna; Mondal, Krishnendu; Sherpa, Mingma Thundu; Thakur, Nagendra (Frontiers in Microbiology, 2022)
Hot springs are thought to be potential repositories for opportunistic infections, such as antibiotic-resistant strains. However, there is a scarcity of information on the mechanisms of antibiotic resistance gene uptake, occurrence, and expression in thermophilic bacteria. Furthermore, because the genesis and proliferation of ARGs in environmental microorganisms is unknown, the research of antibiotic resistance profiles and probable mechanisms in thermophilic bacteria will become increasingly important. The current study's goals are to look at bacterial diversity, antibiotic and heavy metal resistance, as well as the prevalence and presence of antibiotic and metal resistance genes in Geobacillus species. 16S rRNA sequencing was used to determine the culturable bacterium diversity of 124 isolates. Standard Kirby Bauer Disc Diffusion and tube dilution procedures were used to determine antibiotic sensitivity and MIC. The tube dilution method was also used to check metal tolerance. To detect antibiotic and heavy metal resistance genes, whole genome sequencing studies of type species of the genus Geobacillus and 5 randomly selected Geobacillus species were performed. Graph Pad Prism and XLSTAT were used to perform statistical analyses such as ANOVA, EC50 analysis, and PCA. The phylum Firmicutes and the genus Geobacillus dominated the culture-dependent bacterial diversity. Surprisingly, all thermophilic isolates, i.e., Geobacillus species, were sensitive to at least 10 different antibiotics, as evidenced by the lack of antibiotic resistance genes in whole genome sequencing analysis of numerous Geobacillus species. However, some of these isolates were resistant to at least five different heavy metals, and whole genome sequencing revealed the presence of metal resistance genes in these thermophilic bacteria. The thermophilic genus Geobacillus is generally antibiotic sensitive, according to this study. Heavy metal, on the other hand, is tolerated by them. As a result, it's possible that ARGs and MRGs don't coexist in these bacteria living in hot springs.